PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN MOTIVASI BELAJAR IPS SISWA KELAS I SDN 019 AURSATI KECAMATAN TAMBANG KABUPATEN KAMPAR - Tarika Tarika (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by the low motivation to learn IPS students class I SDN 019 Aursati KecamatanTambang Kabupaten Kampar. This research is a research by applying instructional media with the aim toimprove students' IPS learning motivation. This research is a classroom action research conducted at SDN 019Aursati Kecamatan Tambang Kabupaten Kampar. Based on the result of the research, it is found that thestudents' learning motivation has increased every cycle, in the pre cycle the total score of learning motivationobtained by students is 369 with an average of 15 (low), in the first cycle increased to 436 with an average of 18(low) and in the second cycle increased to 693 with an average of 29 (very good). Based on this acquisition canbe concluded that the implementation of image media can increase the motivation of students of class I SDN 019Aursati Kecamatan Tambang Kabupaten Kampar.